Epitope Mapping of Fc gamma RIIa Monoclonal Antibodies - Caroline Tan Sardjono; Bruce Wines; Maree Powel; Mark Hogarth (Universitas Gadjah Mada, 2008)
FcγRIIa (CD32) is an IgG receptor which has been shown to be important in autoimmune disease pathology. IV.3, 8.7, and 7.30 are anti-FcγRIIa monoclonal antibodies (mAbs), which block the interaction between FcγRIIa and complex IgG. In this study, the three mAbs were demonstrated to inhibit FcγRIIa function. The determination of the precise epitopes of the IV.3, 8.7, and 7.30 mAbs may become a potential approach for designing inhibitors for FcγRIIa. The epitope of IV.3, 8.7, and 7.30 were determined using chimeric receptors based on the extracellular domains of FcγRIIa and the FcεRI a chain. The epitopes for IV.3 was found to be mapped on amino acid residues 132-137, while 8.7 and 7.30 were on amino acid residues 112-119 and 157-162. Based on the crystal 3D model of FcγRIIa molecule, these amino acid sequences are clustered together forming a contiguous region within the ligand binding site of the receptor.